THE LEGEND OF THERMO GAME BASED COMPUTER AS INSTRUCTIONAL MEDIA ON THERMOCHEMICAL FOR IMPROVE CURIOSITY - Muhammad Badrul Uyun; Achmad Lutfi (JCER (Journal of Chemistry Education Research), 2022)
This research aims to obtain the learning media as a game of thermochemistry that can improve the curiosity of high school students using The Legend of Thermo game. The Borg and Gall development research model is used as a Research and Development (R&D) method. This model has ten stages which are useful for produced a viable learning media. The result of the validity value is 95.14% with a very valid category. The results of the questionnaire responses of students value is 86.26% with a very practical category. The results of the curiosity assessment of learning students obtained 90.33% with the category of very effective. The significant value of the pretest results obtained 0.200 and posttest results obtained 0.128 which is more than 0.05 so the data are normally distributed. In the Paired Sample t-Test  obtained a significant value of 0,000 which is less than 0.05 so there is a significant difference between the pretest and posttest scores. Based on the description above, The Legend of Thermo game is appropriate to be used as a learning media on Thermochemical material based on the criteria of validity, practicality, and effectiveness.